siRNA-Silencing of swnR gene greatly reduced biosynthesis of swainsonine in Alternaria oxytropis without affecting the growth characteristics of leguminous host - Zhang, Yu; Yang, Liwen; Li, Yange; Tang, Shiyu; Zhang, Yiqingqing; Sun, Pinzhi; Lu, Hao (Frontiers in Microbiology, 2025)
Locoism refers to a neurological disorder in livestock caused by chronic ingestion of locoweeds, which contain toxic alkaloid swainsonine produced by the fungus Alternaria oxytropis. Therefore, reducing swainsonine levels not only prevents locoism but may also transform these toxic plants into animal feed. In this study, we identified a pivotal role for the swnR gene in swainsonine biosynthesis. Using siRNA-mediated gene silencing, we demonstrated that knockdown of swnR markedly reduced swainsonine accumulation in fungal mycelia. Transcriptomic and metabolomic analyses revealed that swnR silencing triggered broad metabolic reprogramming, notably impacting aromatic amino acid metabolism, carbon metabolism, and antioxidative pathways, and underscoring its central role in fungal growth and secondary metabolism. Furthermore, we screened and inoculated a hypovirulent strain suitable for co-cultivation with peeled seed embryos of Oxytropis glabra, and the symbiont showed significantly reduced level of swainsonine without negatively impacting plant growth. These findings provide a promising strategy for mitigating locoism by engineering endophytic fungi with attenuated toxicity.